THE DISCOURSE OF EID 1429AH/2011AD GREETINGS ON THE BANNERS AND BILLBOARDS IN PADANG CITY - Nasrullah Nasrullah; Desy Mardhiah (Graduate Program of Pontianak Institute of Islamic Studies, 2013)
Eid al-Fitr is special compared to other holy days of Muslims. In addition to the celebration of victory for Muslims after a month-long fasting, there is a national phenomenon that occurs ahead of the Eid al-Fitr: the flow of urban people returning to their home towns and villlages. Millions of Muslims in Indonesia return home ahead of the holy day. Padang city or Ranah Minang as the capital of West Sumatra Province is one of the destinations for those homeward-bound travelers since the city and other areas in West Sumatra are the hometowns of the Minang people. Simultaneously, in every public space in the city, banners are installed by the head of the local government, political parties, or community leaders to deliver Eid greetings. This article examines the discourse of the message on the banners in the city of Padang in relation to the reality around the place where the banners were installed, the social context, as well as the relationship between the discourses on the banners. Keywords: Discourse, Eid Greetings